Manajemen Pengembangan Pendidikan Kitab Kuning di Pondok Pesantren Al-Djunaediyah - Nasrullah, Yufi Mohammad; Mutiawan, Dadang; Noorjutstiatini, Witrin; Nazib, Fiqra (Universitas Garut, 2025)
Al Djunaediyah Garut Islamic Boarding School is an institution deeply rooted in the rich tradition of Islamic education in Indonesia. Among its primary educational pursuits, the study of